Distribution patterns of an invasive snail (bithynia tentaculata) in Navigation Pools 7 and 8 of the Upper Mississippi River - Gray, William Paul (My University, 2013)
Since the early 2000's Bithynia tentaculata (Caenogastropodo:Bithyniidae) has invaded the upper Mississippi River drainage system, harboring several species of parasitic trematodes that are killing large numbers of migratory waterfowl. As previous attempts to remove the snails have ben unsuccessful, my study focused on the habitat preferences of B.tentaculata in order to determine which new habitats were vulnerable to invasion.
Keywords: Environmental monitoring -- Mississippi River.; Aquatic ecology.; Water birds -- Diseases -- Mississippi River.; Snails as carriers of disease -- Mississippi River.; Water birds -- Mortality -- Mississippi River.